Minimization of energy consumption in a cryogenic plant through process modification and optimization using a steady state process simulator. - Yunus, Robiah; Wong, S.L.; Abdul Manan, Zainuddin (1995)
This paper describes the process modification and optimization in term of energy saving for the low temperature separation units by using a steady state process simulator. Details of the study are available in full text article.